Diskursus kritis pada isu radikalisme di kalangan mahasiswa di kompas.com - Putra, Javier Maospati Ismail; Farida, Farida (Universitas Dr.Soetomo, 2020)
Campus and understanding of radicalism that supports something new. The emergence of radicalism on campus is not without a long process. Radicalism arises because there is a communication process that occurs with networks that exist outside the campus. The radical stigma in higher education later became a special discussion at the Ministry of Research, Technology and Higher Education. The labeling of several tertiary institutions exposed to radicalism has an impact on the image of tertiary institutions. The reports that make a bad image on campus are allegedly exposed to these radical understandings. College students parents were not silent, some then persuaded to resign from campus. This research has aim to analyze the structure of discourse according to van Dijk in reporting the issue of radicalism among college students on the Kompas.com news portal. In this research, an analysis method with Van Dijk's view will be used. Van Dijk analyzed the text structure with three levels (Macro Structure, Superstructure, Micro Structure) so that the results of the analysis would be sharper. The results of the analysis can conclude that the construct of the news discourse made by Kompas.com in terms of text is included in the live news that is the actual news.Keywords: critical discourse analysis, campus, Kompas.com, radicalism, van Dijk.